Don DeLillo's descent into posthuman anxieties in Zero K and The Silence - Suyoufie, Fadia F.; Dagamseh, Abdullah M. (Orbis litterarum, 2025)
This study provides an exponential reading of the (re)presentation of posthuman technology in relation to human anxieties in Don DeLillo's Zero K (2016), a novel in which technology is very much “alive” and The Silence (2020), in which technology is “dead.” It focuses on DeLillo's apprehension about the impact of technology in relation to everyday life and to the future of humanity. The anxiety over a posthuman existence where Man is reduced to impotence in his total surrender to the control of technology is examined to show DeLillo's concern over the insidious process of dehumanization and depersonalization of the human subject. The discussion is carried out by applying a close textual analysis of the novels within the context of the existential, environmental, and eschatological issues that are considered staples of his narratives. The conclusion affirms DeLillo's stand on the ambiguity of technology and his implicit commitment to ordinary life and to the ethics of human interrelationships as a confirmation of human identity.